TWO MAJOR ISSUES IN DATA GRID REPLICATION PROCESS - Ahmad Raf’ie Pratama (Jurusan Teknik Informatika, Fakultas Teknologi Industri, Universitas Islam Indonesia, 2011)
This paper discusses Data Grid as one of popular application of grid and cloud computing. In Data Grid, data are replicated among different nodes of the grid to increase the availability and efficiency. There are two mainissues regarding this replication process; how to do the replication (i.e. where and when to do replication) and how to synchronise all the replicas under heterogeneous database systems in grids to be always consistent. Thispaper explains those two major issues as well as some proposed methods and solutions in order to explore the next problems and challenges on this area. By identifying them, it can be useful to make some improvements inorder to give the best performance on the replication process, and hence can offer a better experience of Data Grid implementation to the users.